The Influence of Modified Football Games on The Social Development of Elementary School Students - Priyono, Ali (JOURNAL RESPECS (Research Physical Education and Sports), 2023)
This research is motivated by the poor development of adaptation and social respect for students at the elementary school level. The purpose of this study is to determine the effect of modified football games on the social development of elementary school students. The research method used is experimental research with Pre-Experimental design with One Group Pretest-Posttest Design. The population in this study were fifth grade students of SD Negeri 1 Kubangwungu Brebes, totalling 30 students. The sampling technique used Purposive Sampling technique. This research instrument used a questionnaire test with data analysis using normality test, homogeneity test and hypothesis testing using Paired Sample Test. The results of the study based on the analysis of hypothesis testing, this study concluded that there was an effect of modified football games on the social development of students of SD Negeri 1 Kubangwungu Brebes.